The Effect of social media on Values System among Intermediate School Female Students in Tabuk from their Parents’ Point of View (Tik Tok as a model) - Al-Qahtani, Bashayer Dhafr (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the impact of the TikTok application on the values system of middle school students in Tabuk from the point of view of their parents, and to use the survey descriptive curriculum. It was designed as a data collection tool. The study sample was 378 parents of middle-school students in Tabuk city. The results showed that the parents’ response to middle-school students came with an average calculation(3.91),the most prominent dimensions of the impact of TikTok on the values system of middle-school students are the focus of social values at an average (4.28) degree strongly agreed, while the dimension of the ethical values system is second among the dimensions of the values system at an average (4.08) degree approved, and the dimension of personal values is finally among the dimensions of the values system at an average (3.42) degree approved. The absence of statistically significant differences (0.05 ≥ α) between the average responses of the study sample individuals attributable to the variable (type, level of education). statistically significant differences (0.05 ≥ α) between study sample respondents’ averages attributable to job position variability for staff members Based on the results of the study. The researcher recommended to activate the role of the family by monitoring what young people and children watch on the TikTok app and sensitizing them on the risk of social media in general and the TikTok app by holding training sessions in this field both in schools and other nurturing institutions such as mosque, family, school, and media.